Distribution of hepatitis C virus genotype and subtype between Mongolian and Han in Inner Mongolia. Issue 28 (15th July 2022) - Su, Ruijun; Dong, Li; Wang, Yongxiang; Sa, Renna; Wang, Yafei
Abstract : Hepatitis C is a serious infectious disease caused by the hepatitis C virus (HCV). HCV genotypes (GT) and subtypes are closely related to geographical distribution. Studies on the distribution of HCV genotypes can help to understand the regional epidemiology and genotype distribution and provide benefits in the treatment for hepatitis C. To provide information about the distribution of HCV genotypes as well as improved prevention and treatment of hepatitis C, we aimed to classify the distribution of HCV genotypes among Mongolian and Han patients with hepatitis C in Inner Mongolia over the past 5 years. Peripheral blood samples of patients with HCV were collected for gene sequencing. To analyze the HCV genotype distribution and possible influencing factors, we determined the viral load and ratios of various genotypes. We found that the most prevalent genotype in Inner Mongolia was 1b, followed by GT2a, GT3a, GT3b, and GT6a. The prevalence of HCV among Mongolian patients was significantly higher than the prevalence in their Han counterparts ( χ 2 = 16.64, P = .000). There was no significant difference in viral load according to sex among HCV genotypes. However, the viral load of GT 1b was significantly higher than that of GT 2a ( F = 3.51, P = .008). The viral load of GT 1b among ethnic Mongolians was significantly higher than that among Han patients ( t = 2.28, P = .044). The present study's findings can serve as a basis for developing a personalized treatment for hepatitis C among patients in Inner Mongolia.